Pengembangan Media Pembelajaran berbasis Gim Puzzle dan Quiz pada Pelajaran Pemrograman Dasar menggunakan Metode ADDIE - Ngurah Pradipta Surya Mandala; Tri Afirianto; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Basic programming is an important subject to be passed by Vocational High School students whose majors are technology and computer based. In basic programming itself, there are several basic competitions that students must understand, starting with students being required to know various types of programming languages, followed by writing program syntax, understanding data types and constant variables, etc. Learning basic programming requires a lot of practice which can train students to directly engage in programming, as was experienced by SMK National Media Center Malang who found the problem of lack of time to practice due to the Covid-19 pandemic. During the pandemic all teaching and learning activities are always carried out online. Online learning activities like this usually take place assisted by video call media. The existence of this distance constraint means that this learning path will be different from direct learning activities in class, in terms of the flow of material delivery or students' interest and motivation in receiving material.I develop a media that can help students understand Basic Programming lessons. This media will later be in the form of a game based on Android, with a puzzle quiz game style and a material module. This game media was designed using the ADDIE method of Analysis, Design, Development, Implementation, Evaluation. Game media testing will be carried out using 3 methods, namely, using Blackbox testing for the performance of game media functionality, followed by User Acceptance Testing (UAT) to measure the level of user acceptance with the media, and finally a Motivation Questionnaire to measure the level of student learning motivation after using the media.